Strategi Komunikasi Pemasaran Fashion Bekas/Thrift Shop Pada Pasar 18 Kota Binjai - Fauzan Azima Sembiring; Indira Fatra Deni (Program Studi Pendidikan Biologi, 2022)
This study aims to find out how the marketing communication strategy of used fashion / thrift shop in the market of 18 Binjai city. The development of the fashion world today is experiencing a fairly rapid development, especially in Indonesia. The phenomenon of thrift shops, which are also part of the fashion world, has also increased in the level of popularity. This study used qualitative descriptive methods with data collection techniques in the form of interviews, observations and documentation. The data analysis technique in this study uses an analysis model consisting of three main components, namely data reduction, data presentation, and conclusion drawing. The results showed that the marketing communication strategy of used fashion / thrift shop in the market of 18 Binjai cities is a 4P marketing mix strategy consisting of 4 key variables, namely product, price, place / location, and promotion. In products, apply direct marketing strategies or direct marketing and product selection strategies. On the price, apply a discount or discount strategy. In the place / location, implement a location selection strategy that is easy to find, a location that is often passed by the community / visitors, and a convenient location in making sales. On promotion, applying promotion strategies directly and indirectly.